Definition and determination of ozone laminae using Continuous Wavelet Transform (CWT) analysis. (March 2015) - Huang, Guanyu; Newchurch, M.J.; Kuang, Shi; Buckley, Patrick I.; Cantrell, Wesley; Wang, Lihua
Abstract: Ozone laminae result from complex chemical and dynamical processes in the atmosphere. Unfortunately, there is no accepted definition of ozone laminae due to limited knowledge of the science determining their formation and evolution. Current methods to define ozone laminae are based on a reference profile that results from smoothing or linearly-regressing the original profile. These definitions are likely to underestimate the number of ozone laminae in the troposphere because the production of reference profiles reduces the information content in the original profiles. We present a method using the Continuous Wavelet Transform (CWT) with a two-threshold technique to define ozone laminae number and magnitude without requiring a reference profile. Our method encompasses an efficient and robust capability for identifying ozone laminae in the 15-year ozone profiles observed by ozonesondes in Huntsville, AL. Highlights: New definition of ozone laminae employing wavelet analysis. New definition preserves the original information. The characteristics of ozone laminae found by the new definition.